ANALYSIS OF NEW PALM OIL LAND CLEARING PERMITS IN SUBULUSSALAM CITY FROM THE PERSPECTIVE OF MILK AL-DAULAH: A Study on the Encroachment of Leuser Forest Area, Indonesia - Nurhanafi; Azka Amalia Jihad (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2024)
On the island of Sumatra, several provinces have made palm oil a superior commodity, including Aceh Province. Therefore, many people in the Subulussalam region and various parties want to invest in the palm oil agribusiness sector, as a result, various unproductive lands have turned into palm oil lands. The function of the forest, which is the lungs of the earth, is disrupted due to the use of forest areas that are converted into economic land, which of course has a long-term effect on the destruction of the forest itself, which makes the condition of the forest soil will also deteriorate due to the use of fertiliser substances. This study aims to examine and analyse the problem with theoretical and practical approaches regarding the use of the Leuser Forest Area (KEL) as land for oil palm plantations. The research method used is a qualitative research method with a descriptive-analytical approach, data collection techniques are carried out by interview and documentation as well as literature review and regulations related to this research. The results showed that the process of forest encroachment that occurred in the Leuser forest area in Subulussalam City was an illegal activity, because the community cleared oil palm land without going through licensing procedures. Currently, there are approximately 20,000 hectares of illegal oil palm land cleared by residents that have been disciplined. The review of the concept of milk al-daulah on the issue of new palm oil land clearing by the community in the Leuser Forest Area (KEL) is contrary to the concept of milk al-daulah.